Analysis of Financial Management in Kenanga UMKM in Improving Ecobric-Based Economic Welfare (Syari’ah Financial Management Review) - S. Purnamasari; P. Rozak; Kurniaty; A. Hadi; Agus Purnomo (Indonesian Journal of Banking and Financial Technology, 2023)
Indonesia is ranked as the second largest plastic waste producing country in the world. Plastic waste is decomposed within 1 millennium or around 1000 years. Plastic waste has a negative impact on the environment, such as accumulation of rubbish, resulting in environmental pollution. Anticipatory and preventive steps are needed to overcome this problem. One of the right strategies is. We should apply the 3Rs, namely Reduce, Reuse and Recycle in dealing with plastic waste. Management of waste products, if managed well, will have an impact on the community's economy. The problem of this research is how the financial management carried out by Kenanga UMKM is based on ecobricks, a review of sharia financial management and what are the efforts and obstacles of Kenanga UMKM in improving the ecobrick-based economic welfare of its members. This research is research with a qualitative approach with 6 research respondents and the sampling technique uses saturated samples. The data collection technique uses observation, documents and interviews with primary sources, namely the Kenanga UMKM Unit, and secondary source data, namely documents. This research shows that financial management still uses manual and simple recording and is recapped every Saturday. The Kenanga Unit UMKM management is in business development/efforts to improve the welfare of its members.